Evolution of the plankton paleome in the Black Sea from the Deglacial to Anthropocene - Coolen, Marco; Orsi, W.; Balkema, C.; Quince, C.; Harris, K.; Sylva, S.; Filipova-Marinova, M.; Giosan, L. (2013)
The complex interplay of climate shifts over Eurasia and global sea level changes modulates freshwater and saltwater inputs to the Black Sea. The dynamics of the hydrologic changes from the Late Glacial into the Holocene remain a matter of debate, and information on how these changes affected the ecology of the Black Sea is sparse. Here we used Roche 454 next-generation pyrosequencing of sedimentary 18S rRNA genes to reconstruct the plankton community structure in the Black Sea over the last ca. 11,400 y. We found that 150 of 2,710 species showed a statistically significant response to four environmental stages. Freshwater chlorophytes were the best indicator species for lacustrine conditions (>9.0 ka B.P.), although the copresence of previously unidentified marine taxa indicated that the Black Sea might have been influenced to some extent by the Marmara Sea since at least 9.6 ka calendar (cal) B.P. Dinoflagellates, cercozoa, eustigmatophytes, and haptophytes responded most dramatically to the gradual increase in salinity after the latest marine reconnection and during the warm and moist mid- Holocene climatic optimum. According to paired analysis of deuterium/ hydrogen (D/H) isotope ratios in fossil alkenones, salinity increased rapidly with the onset of the dry Subboreal after ~5.2 ka B.P., leading to an increase in marine fungi and the first occurrence of marine copepods. Agradual succession of dinoflagellates, diatoms, and chrysophytes occurred during the refreshening after ~2.5 ka cal B.P. with the onset of the cool and wet Subatlantic climate and recent anthropogenic perturbations.